2022
DOI: 10.1039/d1ee02630e
|View full text |Cite
|
Sign up to set email alerts
|

Flexible polyolefin dielectric by strategic design of organic modules for harsh condition electrification

Abstract: A paradigm-shifting design strategy is demonstrated that unifies the treatment of electronic and conformational properties of polymer dielectrics for concurrent high electric field and elevated temperature harsh conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
67
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(67 citation statements)
references
References 44 publications
(51 reference statements)
0
67
0
Order By: Relevance
“…F‐PI/PCBM delivered a record 709 MV m −1 in E η90 at 150 °C. This is a 29% enhancement versus its pristine counterpart and is 1.34‐ and 1.08‐fold larger than those of PEI/PCBM [ 35 ] and recently reported synthesized novel polymer o ‐POFNB [ 53 ] in E η90 , respectively. It is even comparable to the room‐temperature value (≈700 MV m −1 ) of BOPP.…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…F‐PI/PCBM delivered a record 709 MV m −1 in E η90 at 150 °C. This is a 29% enhancement versus its pristine counterpart and is 1.34‐ and 1.08‐fold larger than those of PEI/PCBM [ 35 ] and recently reported synthesized novel polymer o ‐POFNB [ 53 ] in E η90 , respectively. It is even comparable to the room‐temperature value (≈700 MV m −1 ) of BOPP.…”
Section: Resultsmentioning
confidence: 82%
“…F‐PI/PCBM also provides an E b as high as 815 MV m −1 at 150 °C, which is comparable to the room‐temperature value (≈820 MV m −1 ) [ 6 ] of BOPP. The E b of F‐PI/PCBM at 200 °C delivers an E b of up to 692 MV m −1 , which is much larger than those of F‐PI and PEI/PCBM [ 35 ] and o ‐POFNB [ 53 ] in E b . Notably, pristine F‐PI offers a relatively high E η90 and E b , up to E η90 ≈ 550 MV m −1 and E b ≈ 664 MV m −1 at 150 °C.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The comparison suggests the superior energy storage properties obtained with 5 vol% 2D BNNs/CRC composite films. Therefore, only a few prior research studies 9,42,[46][47][48][49][50][51] are reported achieving U d over 23 J cm À3 accompanied by Z above 80%, e.g., Cd 1Àx Zn x Se 1Ày S y nanodots/PVDF-HFP B 12.5 J cm À3 , 48 P(VDF-TrFE-CFE)/BNNS nanocomposite B9.9 J cm À3 , and a liner dielectric constant of polyoxafluoronorbornene of B6.7 J cm À3 . 49 The stability and reliability of discharged energy density and efficiency for the composite films play a vital role in practical applications.…”
Section: Resultsmentioning
confidence: 99%
“…At 150 °C, POFNB features an unprecedented U e of 5.7 J/cm −3 far outperforming the best reported flexible dielectrics (Wu et al, 2020). Deshmukh et al (2022) prepared a class of POFNB by the versatile ROMP, which is designed by changing the -CF 3 substitution position on the benzene ring to optimize the electrical and thermal properties (Figure 7A). Wide bandgap, freely rotatable structural groups along with a combination of flexible and rigid moieties, achieved through a molecular engineering approach and verified using computational methods resulted in a class of polymer dielectrics with the highest ever discharged energy density (6.5 J/cc) up to 200 °C.…”
Section: The Application Of Romp In Preparation Of Polymer Dielectricmentioning
confidence: 99%